DEVELOPMENT OF INTEGRATED SCIENCE WORKSHEET BASED ON LEARNING CYCLE 5E ON ENERGY IN LIVING SYSTEMS MATERIALS - Intan Puspita Dewi; Skunda Diliarosta (Universe, 2023)
Based on the analysis conducted, it is known that the problems faced in the learning process are that students are not actively involved in the learning process. This is because the methods and teaching materials used have not been able to facilitate students to be actively involved in the learning process. This study aims to produce an integrated science worksheet based on the learning cycle 5E on energy in living systems materials and determine the level of validity and practicality of its use. This type of research is Research and Development (R&D) with the ADDIE development model which is limited to the development stage. The research instrument is a validity and practicality questionnaire. The research data were analyzed using the moment kappa formula. The results of the development stage inform that the LKPD developed is declared valid with the validity value given by the three validators is 0.78 with a high validity category. The developed LKPD is also stated to be practical with the practicality value given by the teacher is 0.98 with a very high practicality category and the practicality value of the students is 0.84 with a very high practicality category.